Imaging crisis in Indigenous Australia and Canada: towards an analysis of neoliberal primitivism. Issue 2 (3rd April 2019) - Hinkson, Melinda; Fullenwieder, Lara
Abstract : The last decade has witnessed a significant shift in the terms through which Indigenous people are rendered visible in public debate in Australia and Canada. In observing the long and recursive history of colonial visual regimes, this paper argues that contemporary politics of Indigenous representation are nevertheless distinctively marked by a regime of neoliberal primitivism . Tracing the features and operations of this regime across a selection of images and discursive imaging practices in Australia and Canada, the paper identifies three tropes that are centrally involved in imaging contemporary Indigenous crises: the suffering child, the silenced woman and the dysfunctional landscape. The visual regime of neoliberal primitivism operationalises these tropes in relation to each other and plays a vital role in the neoliberal turn in Indigenous governance. While bringing attention to the very real forms of damage and distress with which Aboriginal individuals and communities must contend in the present, paradoxically, the paper argues, this regime works to occlude from view the constellation of forces at work in those very circumstances.